2020
DOI: 10.1007/s40534-020-00221-y
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale multi-functional test platform for investigating mechanical performance of track–subgrade systems of high-speed railways

Abstract: Motivated by the huge practical engineering demand for the fundamental understanding of mechanical characteristics of high-speed railway infrastructure, a full-scale multi-functional test platform for high-speed railway track–subgrade system is developed in this paper, and its main functions for investigating the mechanical performance of track–subgrade systems are elaborated with three typical experimental examples. Comprising the full-scale subgrade structure and all the five types of track structures adopte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, due to the limits of the experimental facilities and cost, there is still a lack of the full-scale test regarding the interfacial damage of CRTS II SBTS caused by the vertical wheel impact. ere once was a wheel-drop test of CRTS II SBTS, in which, however, only the acceleration of the track slab was recorded [26]. e development of the interfacial damage was not observed due to technical difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the limits of the experimental facilities and cost, there is still a lack of the full-scale test regarding the interfacial damage of CRTS II SBTS caused by the vertical wheel impact. ere once was a wheel-drop test of CRTS II SBTS, in which, however, only the acceleration of the track slab was recorded [26]. e development of the interfacial damage was not observed due to technical difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 15 ] reported a real-size laboratory test of a double-block ballastless track–subgrade system with emphasis on investigating the dynamic performance evolution. In addition, extensive field tests on investigating the dynamic responses of the railway track–subgrade structure and the ground during train operation have been conducted in some studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], but it is not always practicable, since this method is time-consuming, high-cost, and may interrupt train operations.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted using a systematic approach to investigate the dynamics problems with the train-track-bridge dynamic interaction theory. 5,6,12,[14][15][16][17][18][19][20] By combining each subsystem model and the interaction model between subsystems of the train-track-bridge system into a whole model, the influences of various excitations can be considered or specially studied. [21][22][23][24] For the issues of bridge deformation effects on ballastless tracks, the bridge types investigated are mainly simply-supported girder bridges, continuous girder bridges, and arch bridges.…”
Section: Introductionmentioning
confidence: 99%